Synthesis and biological activity evaluation of a novel pleuromutilin derivative 22-((2-methyl-1-(1H-pyrrole-2-carboxamido)propan-2-yl)thio)-deoxypleuromutilin - Li, Zhun; Ma, Danqian; Liu, Chang; Qin, Zhe; Bai, Lixia; Ge, Wenbo; Xu, Xiao; Li, Jianyong (Frontiers in Pharmacology, 2025)
Objective and methodsWidespread antibiotic misuse has resulted in growing antimicrobial resistance, diminishing the clinical efficacy of existing antibiotics against resistant strains. Therefore, we designed and synthesized a novel pleuromutilin derivative PDP, and its antibacterial activities were evaluated in vitro and in vivo.ResultsPDP exhibited potent antibacterial activity against Gram-positive bacteria (MRSA, MRSE, Staphylococcus aureus, Streptococcus agalactiae and Staphylococcus dysgalactiae), demonstrating a remarkably low MIC of 0.008 μg/mL, which was superior to both reference drugs tiamulin and valnemulin. Moreover, compared to tiamulin, it displayed a slower rate of resistance development. Molecular docking results demonstrate that PDP exhibits favorable binding to the peptidyl transferase center. The inhibition of bacterial protein synthesis by PDP was indirectly demonstrated through GFP expression inhibition assays. Derivative PDP exhibited extremely low cytotoxicity and had low oral acute toxicity, with an LD50 exceeding 2,000 mg/kg of body weight. When tested in a mouse model of systemic infection, PDP demonstrated superior efficacy to tiamulin and comparable activity to valnemulin. The bacterial carrier load indicated that PDP possessed significant efficacy in mitigating tissue damage resulting from MRSA infection in the lung, kidney, and liver.ConclusionConsequently, PDP is a promising compound that may be useful for the development of therapeutic applications in the future.